PENINGKATAN HASIL BELAJAR MATEMATIKA MATERI SUDUT MELALUI MODEL PEMBELAJARAN KOOPERATIF JIGSAW - Sulistyarini; Wathi, Ayu Fahimah Diniyah (Prosiding Temu Ilmiah Nasional Guru, 2023)
The research objective was to determine the effect of applying the jigsaw learning model to improve the mathematics learning outcomes of third grade students at SD Negeri 2 Selogiri on Angle material. The research method uses classroom action research (PTK) with the Kemmis and Mc Taggart models, which consist of two cycles, namely Cycle I and Cycle II, which are arranged into four stages, namely planning, implementing, observing, and reflecting. Student worksheets, question cards, and student performance observation forms were used as data collection tools. In pre-cycle learning with 16 students, 8 students achieved KKM with an average of 60.62 and a completeness level of 50%. Cycle I increased to 11 students with an average score of 70.6 and a completeness level of 68.7%. Then it increased to 14 students in cycle II who passed the KKM with an average score of 81.25 and a completeness level of 87.5%. It is known that learning through the jigsaw learning model can improve student learning outcomes.